2014
DOI: 10.17795/ajcmi-19216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metallo-β-lactamases Encoding Genes Among Pseudomonas aeruginosa Strains Isolated From the Bedridden Patients in the Intensive Care Units

Abstract: Background:Pseudomonas aeruginosa is one of the most important agents causing nosocomial infections worldwide. Multidrug resistance of isolated bacteria from nosocomial infections makes it difficult and sometimes impossible to treat. Objectives: The aim of the present study was to investigate the antibiotic resistance and association between blaIMP and blaVIM genes with resistance to meropenem and imipenem among P. aeruginosa strains isolated from Iranian patients in ICU wards of Hamadan, IR Iran. Patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…However, not only the sputum isolates of this study were resistant to all antibiotics tested, but also 11 (42.3%) of them were detected as MDR. On the other hand, our clinical isolates had a relatively low resistance rate (< 40%) against all antibiotics tested, except gentamicin, as well as other Iranian studies (3,16). However, the studies conducted by Radan et al in 2016, and Mirsalehian et al in 2017, reported the higher antibiotic resistance rate (5,13), may be due to the type of samples, as all isolates collected from burn sections.…”
Section: Discussionsupporting
confidence: 40%
“…However, not only the sputum isolates of this study were resistant to all antibiotics tested, but also 11 (42.3%) of them were detected as MDR. On the other hand, our clinical isolates had a relatively low resistance rate (< 40%) against all antibiotics tested, except gentamicin, as well as other Iranian studies (3,16). However, the studies conducted by Radan et al in 2016, and Mirsalehian et al in 2017, reported the higher antibiotic resistance rate (5,13), may be due to the type of samples, as all isolates collected from burn sections.…”
Section: Discussionsupporting
confidence: 40%
“…Nosocomial outbreaks caused by MBL-producing P. aeruginosa have been reported in different hospital units of our country such as many countries worldwide. [ 10 11 ] Carbapenemases that hydrolyze carbapenems and make them inactive have been progressively reported in Asia and Europe, Canada, and the United States. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…As prevalence of infectious diseases have been decreasing during last decades (13), but the drug resistance became an important issue regarding the treatment of such diseases (7,8,14,15). Drug resistance in Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 99%